Fasting increases the phosphorylation of AMPK and expression of sirtuin1 in muscle of adult male northern elephant seals (Mirounga angustirostris). - Lee, Debby; Martinez, Bridget; Crocker, Daniel E; Ortiz, Rudy M (eScholarship, University of California, 2017)
Fasting typically suppresses thyroid hormone (TH)-mediated cellular events and increases sirtuin 1 (SIRT1) activity. THs may regulate metabolism through nongenomic pathways and directly through activation of adenosine monophosphate-activated protein kinase (AMPK). Adult male elephant seals (Mirounga angustirostris) are active, hypermetabolic, and normothermic during their annual breeding fast, which is characterized by stable TH levels. However, the contribution of TH to maintenance of their fasting metabolism is unknown. To investigate the fasting effects on cellular TH-mediated events and its potential association with SIRT1 and AMPK, we quantified plasma TH levels, mRNA expressions of muscle SIRT1 and TH-associated genes as well as the phosphorylation of AMPK in adult, male northern elephant seals (n=10/fasting period) over 8weeks of fasting (early vs. late). Deiodinase type I (DI1) expression increased twofold with fasting duration suggesting that the potential for TH-mediated cellular signaling is increased. AMPK phosphorylation increased 61±21% with fasting suggesting that cellular metabolism is increased. The mRNA expression of the TH transporter, monocarboxylate transporter 10 (MCT10), increased 2.4-fold and the TH receptor (THrβ-1) decreased 30-fold suggesting that cellular uptake of T4 is increased, but its subsequent cellular effects such as activation of AMPK are likely nongenomic. The up-regulation of SIRT1 mRNA expression (2.6-fold) likely contributes to the nongenomic activation of AMPK by TH, which may be necessary to maintain the expression of PGC-1α These coordinated changes likely contribute to the up-regulation of mitochondrial metabolism to support the energetic demands associated with prolonged fasting in adult seals.